Development of an Inflammatory CD14+ Dendritic Cell Subset in Humanized Mice - Iwabuchi, Ryutaro; Ide, Keigo; Terahara, Kazutaka; Wagatsuma, Ryota; Iwaki, Rieko; Matsunaga, Hiroko; Tsunetsugu-Yokota, Yasuko; Takeyama, Haruko; Takahashi, Yoshimasa (Frontiers in Immunology, 2021)
Humanized mouse models are attractive experimental models for analyzing the development and functions of human dendritic cells (DCs) in vivo. Although various types of DC subsets, including DC type 3 (DC3s), have been identified in humans, it remains unclear whether humanized mice can reproduce heterogeneous DC subsets. CD14, classically known as a monocyte/macrophage marker, is reported as an indicator of DC3s. We previously observed that some CD14+ myeloid cells expressed CD1c, a pan marker for bona fide conventional DC2 (cDC2s), in humanized mouse models in which human FLT3L and GM-CSF genes were transiently expressed using in vivo transfection. Here, we aimed to elucidate the identity of CD14+CD1c+ DC-like cells in humanized mouse models. We found that CD14+CD1c+ cells were phenotypically different from cDC2s; CD14+CD1c+ cells expressed CD163 but not CD5, whereas cDC2s expressed CD5 but not CD163. Furthermore, CD14+CD1c+ cells primed and polarized naïve CD4+ T cells toward IFN-γ+ Th1 cells more profoundly than cDC2s. Transcriptional analysis revealed that CD14+CD1c+ cells expressed several DC3-specific transcripts, such as CD163, S100A8, and S100A9, and were clearly segregated from cDC2s and monocytes. When lipopolysaccharide was administered to the humanized mice, the frequency of CD14+CD1c+ cells producing IL-6 and TNF-α was elevated, indicating a pro-inflammatory signature. Thus, humanized mice are able to sustain development of functional CD14+CD1c+ DCs, which are equivalent to the human DC3 subset observed in humans, and they could be useful for analyzing the development and function of DC3s in vivo.